Development Of Mobile Application Based On Crowdsourcing For Car Rental Management By Using Scrum Methodology (customer Side) - Komang Aditya Respa Putra; Soni Fajar Surya Gumilang; Muhammad Azani Hasibuan (eProceedings of Engineering, 2015)
Abstract – Indonesia has about 250 million people. Mostly, Indonesian people not facilitated by private car [1] so when they are traveling outside the city they usually use motorcycle. The other alternative is public transportation, but most of the public transportation in Indonesia uncomfortable based on a survey conducted in this research. Base on this condition, the car rental business become popular among Indonesia people to meet their needs of vehicle for travel even though out of the city. However, the dissemination of information regarding the rental car itself is still done through banners, brochures and newspaper ads that make the dissemination of information about car rental is not effective. In fact, Indonesia people mostly has a smartphone that certainly can be used to get information faster. Dissemination of information through printed media can be transferred through digital media so make it spread out more quickly, especially information regarding the car rental through the website or mobile application. In this research will be discussed on the development of mobile applications based on crowdsourcing for the management car rental. With this application, dissemination of information about car rental can be centralized in a single application. In addition, there is a feature to give some comments to certain car from rental. If the prospective renter still doubt to hire a car, prospective renter can see the review that given by other users to determine whether a rental has a good reputation or not. Keyword: Car rental, crowdsourcing, e-commerce, mobile application, scrum methodology.